Knowledge, attitude, and quality of life among newly diagnosed type 2 diabetic patients attending diabetic clinics at Bugando Medical Centre, Mwanza, Tanzania - Rweyendera, Allen; Gwahula, Greyson; Alexander, Faraja; Vedastus, Yacinter; Maziku, Raymond; Mukama, Monica; Silas, Edwin; Kafumu, Illuminata; Ngerecha, Alphonce; Tuwa, Ally; Chilipweli, Peter; Jaka, Hyasinta; et al. (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundDiabetes mellitus, particularly type 2 diabetes, is a rapidly escalating global health issue. The World Health Organization projects a significant increase in diabetes prevalence worldwide, especially in developing countries. Various studies have explored the prevalence and impact of type 2 diabetes, revealing significant geographical disparities in the incidence and management of the disease. However, the extent to which knowledge and attitude influence newly diagnosed patients, particularly in low-resource settings like Mwanza, Tanzania, remains underexplored. Thus, the aim of this study was to assess the knowledge, attitude, and quality of life among newly diagnosed type 2 diabetic patients attending diabetic clinics at Bugando Medical Centre (BMC) in Mwanza, Tanzania.MethodsA cross-sectional survey was conducted among newly diagnosed type 2 diabetic patients attending BMC diabetic clinics from September 2024 to November 2024. Data were collected using a structured questionnaire that includes validated instruments such as the Diabetes Knowledge Test (DKT), the Diabetes Attitude Scale (DAS), and the WHOQol for measuring quality of life (QoL). The questionnaire captured demographic and clinical characteristics data, diabetes knowledge, attitudes toward the disease, and QoL indicators. Statistical analysis was performed to identify correlations between knowledge, attitude, and QoL.ResultsThis study involved 150 newly diagnosed type 2 diabetic patients at Bugando Medical Centre. The median age was 62 years (IQR 57–68), with 63.3% female patients and 92% married. Most participants had primary education (49.7%) and resided in urban areas (82%). Clinically, 66% had hypertension, and the median BMI was 28.4 kg/m², indicating overweight/obesity. The median HbA1c level was 7.4% (IQR 6.9–8.8). In terms of knowledge, the median score was 9 (IQR 7–10), with 69.3% having moderate knowledge, 29.3% high knowledge, and 1.3% low knowledge. Education level influenced knowledge, with 78.4% of primary-educated patients having moderate knowledge, while 42.6% of those with secondary education had high knowledge. Regarding attitude, 54.9% exhibited a negative attitude, with 61.3% feeling inferior due to diabetes and 64% struggling with daily disease management. However, 50% felt things were going well, and 48% believed diabetes had minimal impact on their lives. QoL varied across domains: the physical health mean score was 3.1 (SD ± 0.56), psychological 3.2 (SD ± 0.61), social 3.7 (IQR 2.7–3.7), and environmental 2.99 (SD ± 0.53). The overall QoL median score was 3.2 (IQR 2.8–3.5), indicating average wellbeing, with challenges in the environmental domain requiring targeted interventions.ConclusionThis study highlights the significant challenges faced by newly diagnosed type 2 diabetic patients at Bugando Medical Centre, including knowledge gaps, negative attitudes, and poor quality of life, particularly in the physical and environmental domains. The findings emphasize the need for comprehensive educational initiatives and psychological support to enhance self-management. Targeted interventions, especially for vulnerable groups like female patients, along with a multidisciplinary care approach, can improve diabetes management and overall wellbeing.